Adult Students’ Attitudes Towards Distance Learning During the SARS-Co-V-2 Virus Pandemic - Rodek, Violetta; Orlińska, Anna (International Journal of Research in E-learning, 2021)
The article is a study report on distance learning during the SARS-Co-V-2 virus pandemic, conducted among postsecondary school students. The subject of the study was the opinions of postsecondary school students about distance learning. The research was diagnostic in nature, and the method of a diagnostic poll with survey technique was used. The author’s survey was sent to 85 students of postsecondary schools in the Opole voivodship (Poland). As a result of the study, an average level of satisfaction, degree of motivation and involvement in self-learning by the respondents was determined, as well as an average evaluation of the level of effectiveness of learning conducted in that form. The respondents indicated both the positive and negative aspects of distance learning. The first group comprised mainly aspects related to saving time, money and the flexibility of this form of learning, while the other group included aspects of a social and health nature, related to shortcomings in self-study and evaluation of the learning process.